VĀSTUVIMARŚA IN MATSYAPURĀṆA - M. Kishan; Shankar, Uma (ShodhKosh: Journal of Visual and Performing Arts, 2023)
At the beginning of creation, following the primary creation (mukhya-sarga) and the creation of plants and animals (the tiryak-sarga), Brahmā created human beings endowed with intellect. Just as animals require shelter to protect themselves from cold, wind, and other natural forces, so too do humans need a dwelling place. Based on their economic condition, people construct homes according to their means. Although the subject of house construction is mentioned in the Vedas in various contexts, the detailed nature and guiding principles of such construction have been elaborated only in the Purāṇas and related treatises. This specialized knowledge came to be known as the science of architecture — Vāstuśilpa or Vāstuśāstra